The role of the ideotype in future agricultural production - Carbajal-Friedrich, Alonso A. J.; Burgess, Alexandra J. (Frontiers in Plant Physiology, 2024)
The crop ideotype was first defined by Donald (1968) as an idealised structural model of a plant which can theoretically attain maximum yield quantity and quality within a given environment. Many of the major crop species have proposed ideotypes. For example, in wheat (Triticum aestivum), suggested characteristics include a short strong stem, few erect, small leaves and large ears. Breeding for crop ideotypes is a continuous process as beneficial traits are updated to match current needs. Government organisations such as the Agriculture and Horticulture Development Board (AHDB) in the United Kingdom, publish a recommended list of varieties each year, and so we hypothesise that these recommended varieties will express traits of the ideotype. However, through greenhouse experiments, we show that three recent AHDB recommended wheat varieties differ to that of the ideotype and to each other. This either indicates that the concept may not be universal, or the main target for breeding programmes; that traits may not have successfully been bred yet; or, that other conflicting reasons may be preventing the expression of the ideotype. To this end, we review the factors that may influence plant structure before discussing new tools and methods that can aid ideotype design. Through this paper, we argue that whilst there are benefits to the concept of the ideotype, the 'power' of the concept is lost when integrating the multitude of factors that, in combination, determine plant structure and function in a given environment. Nevertheless, regardless of these limitations, we argue that there is still a role for the ideotype in crop breeding, but that this concept needs to be expanded to emphasise the genetic and environmental interactions that influence plant physiology.